Stiffness reduction index for detection of damage location: Analytical study - Fayyadh, M.M.; Razak, H.A. (2011)
A new damage location index is developed and presented in this paper. The new index is based on the combined mode shape vector and its derivatives to overcome the problem of inaccuracy and insensitivity of existing indices to locate damage in a beam-like structure model. The proposed new index called the stiffness reduction index (SRI) is computed based on the change in eigenvectors and its curvature at each element and for individual mode shapes. In order to assess the validity of the new index, comparisons with an existing algorithm, that is, the co-ordinate model assurance criteria (COMAC) were undertaken using modal data from a finite element model. The study has adopted the first four bending modes to examine the sensitivity of both existing as well as developed damage location indices. The study has examined the new damage index for very small damage intensity, which has been presented by reducing the modulus of elasticity at certain elements along the beam length by only 1. The results obtained from this study revealed higher and better sensitivity of the developed index to detect a low damage intensity and at different locations along the length of the beam. The study has validated the new index to detect the damage location for the case of multi damage location presented at the same time along the beam length. In addition, the index is more adept and managed to resolve the inadequacies of the COMAC index. Â© 2011 Academic Journals.